2021
DOI: 10.1126/science.abi7730
|View full text |Cite
|
Sign up to set email alerts
|

Seismic detection of the martian core

Abstract: Clues to a planet’s geologic history are contained in its interior structure, particularly its core. We detected reflections of seismic waves from the core-mantle boundary of Mars using InSight seismic data and inverted these together with geodetic data to constrain the radius of the liquid metal core to 1830 ± 40 kilometers. The large core implies a martian mantle mineralogically similar to the terrestrial upper mantle and transition zone but differing from Earth by not having a bridgmanite-dominated lower ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
282
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 233 publications
(349 citation statements)
references
References 121 publications
23
282
1
1
Order By: Relevance
“…The amount of light elements in the core, particularly important for a better understanding of Venus's magnetic field evolution and also informative about Venus's conditions during core formation, is not known. The two parameters together, k 2 and MOIF, help to better distinguish the models as has already been shown, for example, for Mars (Rivoldini et al 2011; and recently confirmed with InSight seismic data by Stähler et al 2021), and thus better than in the models of Dumoulin et al (2017), for which MOIFs were assumed to be unknown. The information about the density distribution from the MOIF is not unique, i.e., for the same MOIF the core can be small and dense or relatively larger and lighter.…”
Section: Resultssupporting
confidence: 62%
“…The amount of light elements in the core, particularly important for a better understanding of Venus's magnetic field evolution and also informative about Venus's conditions during core formation, is not known. The two parameters together, k 2 and MOIF, help to better distinguish the models as has already been shown, for example, for Mars (Rivoldini et al 2011; and recently confirmed with InSight seismic data by Stähler et al 2021), and thus better than in the models of Dumoulin et al (2017), for which MOIFs were assumed to be unknown. The information about the density distribution from the MOIF is not unique, i.e., for the same MOIF the core can be small and dense or relatively larger and lighter.…”
Section: Resultssupporting
confidence: 62%
“…Assuming an active context of dike and fracture propagation along Cerberus Fossae, we can expect that most of the seismicity will be located at shallow depth, since on Earth it occurs mostly between the upper dike top and the surface (Ágústsdóttir et al, 2016;Passarelli et al, 2015;Rubin & Gillard, 1998;Ukawa & Tsukahara, 1996). However, the estimated first results from the InSight mission suggest hypocentral depths of 20-30 km for the main events (e.g., Brinkman et al, 2021;Stähler et al, 2021). On the other hand, the lateral propagation of the system toward the east implies that the seismicity could be also located at depth near the propagating dike tips (Green et al, 2015;Rubin & Gillard, 1998;Sigmundsson et al, 2015).…”
Section: Regional and Local Stress Concentrations: Constraints On Marsquake Locations Recorded By The Insight Missionmentioning
confidence: 99%
“…Seismic recordings collected on the Moon and Mars by the Apollo and InSight mission (e.g., Banerdt et al, 2020;Lognonné et al, 2019Lognonné et al, , 2020Nunn et al, 2020) have provided direct information on the interior structure of both planetary bodies from crust (e.g., Kovach and Watkins, 1973;Toksöz et al, 1974) to core (Garcia et al, 2011;Stähler et al, 2021;Weber et al, 2011). RF analysis of these data has led to important insights.…”
Section: Introductionmentioning
confidence: 99%